2008
DOI: 10.1002/ejsp.504
|View full text |Cite
|
Sign up to set email alerts
|

How does intergroup contact reduce prejudice? Meta‐analytic tests of three mediators

Abstract: Recent years have witnessed a renewal of interest in intergroup contact theory. A meta-analysis of more than 500 studies established the theory's basic contention that intergroup contact typically reduces prejudices of many types. This paper addresses the issue of process: just how does contact diminish prejudice? We test meta-analytically the three most studied mediators: contact reduces prejudice by (1) enhancing knowledge about the outgroup, (2) reducing anxiety about intergroup contact, and (3) increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

139
2,020
12
91

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 2,176 publications
(2,262 citation statements)
references
References 42 publications
139
2,020
12
91
Order By: Relevance
“…Beyond the moderation effects, the association between contact and attitudes was shown to be mediated by empathy and anxiety, findings which reflect those reported in previous research [8]. These findings therefore add to the evidence base indicating that empathy and anxiety are important components to consider when developing interventions based on contact [8].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Beyond the moderation effects, the association between contact and attitudes was shown to be mediated by empathy and anxiety, findings which reflect those reported in previous research [8]. These findings therefore add to the evidence base indicating that empathy and anxiety are important components to consider when developing interventions based on contact [8].…”
Section: Discussionsupporting
confidence: 85%
“…These findings therefore add to the evidence base indicating that empathy and anxiety are important components to consider when developing interventions based on contact [8]. For example, interventions promoting positive attitudes towards disability amongst children may focus on methods for creating real or imagined contact situations that enhance children's empathy and reduce anxiety about interacting with children with disabilities.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The classic intergroup contact hypothesis states that positive interaction (i.e., contact) between members of different groups (e.g., through intergroup friendships, Pettigrew, 1997 (Pettigrew & Tropp, 2008, in addition to threat reduction, their meta-analysis identified empathy and knowledge of the immigrant outgroup as mediators; see Binder et al, 2009, for longitudinal evidence of threat reduction as a mediator). A study in Italy showed that intergroup anxiety decreased with increasing contact which then reduced prejudice toward African immigrants (Voci & Hewstone, 2003).…”
Section: Perceived Threat and Intergroup Contactmentioning
confidence: 99%
“…La liste des conditions favorables ou nécessaires aux contacts intergroupes n'a cessé de s'allonger dans la deuxième moitié du 20 e siècle. Des auteurs comme Pettigrew (1998 ;Pettigrew et Tropp, 2008) et Dovidio, Gaertner et Kawakami (2003) ont effectué des recensions de ces éléments essentiels tels que : la gestion de l'anxiété causée par ces contacts (Islam et Hewstone, 1993 ;Wilder et Shapiro, 1989 ;Stephan et White Stephan, 1985) ; la fréquence et la durée des rencontres (Cook, 1984 ;Wilder et Thompson, 1980 ;Worchel, Andreoli et Folger, 1977 ;Zajonc, 1968) ; un contexte qui permet d'avoir des relations personnalisées (Brewer et Miller, 1988 ; la création d'une identité supra-ordonnée rassembleuse (Gaertner, Mann, Murrell et Dovidio, 1989 ;Gaertner et coll., 1994) ; et le caractère plaisant des rapports (Wilder, 1984). De même, les recherches récentes sur les contacts entre francophones et anglophones au Québec (Côté, 2005 ;Pagé, Côté et Lasry, 2007) montrent que ceux-ci ont des particularités liées au caractère linguistique de ces contacts, notamment l'importance du sentiment de compétence dans leur langue seconde sur l'anxiété des participants lors des contacts.…”
Section: La Théorie Des Contacts Intergroupesunclassified